Investigating the role of immune-endocrine alterations during type 2 diabetes associated with changes in Mycobacterium tuberculosis growth - Klazen, Jessica (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.